SISTEM PSIKOTEST UNTUK REKRUTMEN DAN KENAIKAN JABATAN DI PT. ELECTRONIC DATA INTERCHANGE INDONESIA - Mohammad Luthfie Febrian, (2023)
Recruitment activities are the search and withdrawal of prospective employees to join and occupy jobs in accordance with the main tasks in an organization or company. Psikotest is one of the tests conducted to measure the psychological aspects of individuals. This test can be in the form of written, projective, or administered verbal evaluations to measure a person's cognitive and emotional functions or abilities. In psychological tests, the ability that is measured does not tend to be related to a person's IQ. Besides the IQ test there is also a personality test. The current problem at PT Electronic Data Interchange Indonesia is that the system for the recruitment process for prospective new employees and for employees who will be promoted has not yet been structured. For the recruitment process for new prospective employees where to get employees who are competent and have expertise in their fields is still manual using a Google form which is given a duration of processing time so that the recruitment process takes quite a long time. For employees who are promoted, they still use other vendors which require a lot of very large costs. The result of this research is the creation of a psychological test information system for recruitment and employees who will be promoted to facilitate the recruitment process and employees who will be promoted.